Solvent retention, thermodynamics, rheology and small angle x-ray scattering studies on thermoreversible poly(vinylidene fluoride) gels - Yadav P.J.P.; Patra A.K.; Sastry P.U.; Ghorai B.K.; Maiti P. (My University, 2025)
Solvent retention power of poly(vinylidene fluoride) (PVDF) gels has been studied for various homologues of phthalate (aromatic diesters). The thermal stability has been examined for gels of varying morphology. Solvent evaporation, gelation, gel melting, and polymer degradation temperatures have increased with increasing aliphatic chain length of phthalates. The thermodynamics and polymer-solvent compound formations in the PVDF-phthalate gels have been explored. The weight fraction of polymer in compound has decreased with increasing aliphatic chain length. SAXS studies have confirmed the lamellar organization inside the fibrils, and interlamellar distance increases with aliphatic chain length of diesters. The scattering patterns follow the power law behavior (I(q) ≃ q-α), and polymer gels consist of high-density mass (fibril), voids, and interlamellar region. Dynamic mechanical properties indicate the splintering and reformation of network structure in gels whose percolation frequency has reduced for higher aliphatic chain length phthalate. Morphology-dependent moduli have been observed, and greater mechanical strength has been verified for thicker fibrillar gels both for steady and dynamic measurements. © 2010 American Chemical Society.